Comparison of biologics and small-molecule drugs in axial spondyloarthritis: a systematic review and network meta-analysis - Zhou, Erye; Wu, Jian; Zeng, Keqin; Wang, Mingjun; Yin, Yufeng (Frontiers in Pharmacology, 2023)
Background: Biologics and small molecule drugs are becoming increasingly welcomed worldwide in treatment of axial spondyloarthritis (axSpA), including ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). However, a quantitative multiple comparison of their efficacy and safety is lacking. This study aims to provide an integrated assessment of the relative benefits and safety profiles of these drugs in axSpA treatment. Methods: We included randomized clinical trials that compared biologics and small molecule drugs in the treatment of axSpA patients. The primary outcomes assessed were efficacy, including the Assessment of SpondyloArthritis International Society (ASAS) improvement of 20% (ASAS20) and 40% (ASAS40). Safety outcomes included treatment-emergent adverse events (TEAEs) and serious adverse events (SAEs). We used the surface under the cumulative ranking curve (SUCRA) value and ranking plot to evaluate and rank clinical outcomes and safety profiles of different treatments. The two-dimensional graphs were illustrated to visually assess both efficacy (horizontal axis) and safety (vertical axis) of each intervention. Results: Our analysis included 57 randomized clinical trials, involving a total of 11,787 axSpA patients. We found that seven drugs (TNFRFc, TNFmAb, IL17Ai, IL17A/Fi, IL17RAi, JAK1/3i, and JAK1i) were significantly more effective in achieving ASAS20 response compared to placebo (PLA). Except for IL17RAi, these drugs were also associated with higher ASAS40 responses. TNFmAb demonstrated the highest clinical response efficacy among all the drugs. Subgroup analyses for AS and nr-axSpA patients yielded similar results. IL17A/Fi emerged as a promising choice, effectively balancing efficacy and safety, as indicated by its position in the upper right corner of the two-dimensional graphs. Conclusions: Our findings highlight TNFmAb as the most effective biologic across all evaluated efficacy outcomes in this network meta-analysis. Meanwhile, IL17A/Fi stands out for its lower risk and superior performance in achieving a balance between efficacy and safety in the treatment of axSpA patients.